(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Goods and Service Tax GST is all set to be a game changer for the Indian economy. The tax is expected to reduce the concept of ‘tax on tax’, increase the gross domestic product of the economy and reduce prices. In India, there are different indirect taxes applied on goods and services by central and state government. GST is intended to include all these taxes into one tax with seamless ITC and charged on both goods and services. For the introduction of GST, the Government needs to get the Constitution Amendment Bill passed so that the proposed objective of subsuming all taxes and allowing states to tax subjects in Union list and vice versa is achieved. Without these powers, it is not legally possible to move towards GST. Conceptually GST is expected to have numerous benefits like reduction in compliances in the long run since multiple taxes will be replaced with one tax. It is expected to bring down prices and hence the inflation since it will remove the impact of tax on tax and enable seamless credit.